Immunogenicity and safety of coadministration of COVID-19 and influenza vaccination. Issue 1 (5th January 2023) - Wagenhäuser, Isabell; Reusch, Julia; Gabel, Alexander; Höhn, Anna; Lâm, Thiên-Trí; Almanzar, Giovanni; Prelog, Martina; Krone, Lukas B.; Frey, Anna; Schubert-Unkmeir, Alexandra; Dölken, Lars; Frantz, Stefan; et al.
Seasonal influenza vaccination is established as important infection prevention measure, especially among highly exposed healthcare workers (HCWs) [1]. Coadministration with the third dose of COVID-19 vaccine could be an efficient strategy protecting HCWs from two major viral respiratory infections [2–4]. To date, the humoral immunogenicity and side-effects of a coadministered third COVID-19 and a seasonal quadrivalent influenza vaccine are still unclear, and the available data is limited in transferability to the general public [5–7]. This preference-based non-randomised controlled study examines the antibody-mediated immunogenicity and vaccine-related side-effects of mRNA-based COVID-19 and seasonal influenza vaccine coadministration in HCWs. Coadministration of seasonal quadrivalent influenza and COVID-19 booster vaccination is safe and does not increase vaccine-related side-effects, but may limit anti-SARS-CoV-2 antibody formation https://bit.ly/3uKFUie